PENILAIAN KEPUTUSAN INVESTASI SAHAM DALAM PENERAPAN INSENTIF PAJAK PENJUALAN ATAS BARANG MEWAH (PPnBM) BAGI PERUSAHAAN GO PUBLIC DI ERA PANDEMI COVID-19 (STUDI KASUS PADA PERUSAHAAN SEKTOR OTOMOTIF) - Liwe, Alther Gabriel; Budiarso, Novi Swandari; Pontoh, Winston (Universitas Sam Ratulangi, 2021)
In the midst of the Covid-19 pandemic, investors need to see and assess the level of risk to determine investment decisions. With various government policies, especially the Sales Tax Incentive on Luxury Goods (PPnBM), we can assess and compare the level of risk and risk before the issuance of this regulation, so that investors can make the best investment decisions in the midst of the Covid-19 pandemic. The stock beta for the automotive sector was still stable when the PPnBM incentive was implemented, as shown by the calculation of the CAPM Capital Asset Pricing Model, which is mostly below 1. The impact of the Covid-19 pandemic is still felt in world investment and tends to improve over time.